Psychotherapy relationships that work : evidence-based responsiveness - Norcross, John C., 1957- (New York ; Oxford : Oxford University Press, 2011)
Assembles the understanding on the critical relationship between the clinician and the patient into one volume. Researchers and clinicians examined empirical research as well as the evidence-based practices that may be used to cultivate and customize the clinician-patient relationship.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Psychotherapist and patient; Psychotherapy